Action Congruency Influences Crowding When Discriminating Biological Motion Direction. (September 2016) - Ikeda, Hanako; Watanabe, Katsumi
Identification and discrimination of peripheral stimuli are often difficult when a few stimuli adjacent to the target are present (crowding). Our previous study showed that crowding occurs for walking direction discrimination of a biological motion stimulus. In the present study, we attempted to examine whether action congruency between the target and flankers would influence the crowding effect on biological motion stimuli. Each biological motion stimulus comprised one action (e.g., walking, throwing wastepaper, etc.) and was rotated in one of five directions around the vertical axis. In Experiment 1, observers discriminated between the directions of the target stimulus actions, which were surrounded by two flankers in the peripheral visual field. The crowding effect was stronger when the flankers performed the same action as the target and the directions differed. The congruency of action type enhanced the crowding effect in the direction-discrimination task. In Experiment 2, observers discriminated between action types of target stimuli. The crowding effect for the action-discrimination task was not modulated by the congruency of action direction. Thus, identical actions induced a larger crowding effect for action-direction discrimination, but congruent directions did not influence crowding for action-type discrimination. These results suggest that the processes involved in direction discrimination of biological motion are partially distinct from action discrimination processes.